TEACHER'S SELF-DEVELOPMENT AS A CONTINUOUS PROCESS - Mirkhalilova Nargiza Akbarovna (Western European Studies, 2025)
This article explores teacher self-development as a continuous, conscious, and systematic process aimed at enhancing professional, intellectual, methodological, and personal competencies. Self-development is interpreted as a lifelong learning activity through which teachers analyze their strengths and weaknesses, set development goals, and improve their pedagogical skills. The study outlines key stages of self-development, including self-diagnosis, planning, practical implementation, and self-assessment, emphasizing the importance of reflection, intrinsic motivation, and professional competence
Keywords: Teacher; self-development; professional competence; peflection